Natronolimnobius sulfurireducens sp. nov. and Halalkaliarchaeum desulfuricum gen. nov., sp. nov., the first sulfur-respiring alkaliphilic haloarchaea from hypersaline alkaline lakes. Issue 9 (5th June 2019) - Sorokin, Dimitry Y.; Yakimov, Mikhail; Messina, Enzo; Merkel, Alexander Y.; Bale, Nicole J.; Sinninghe Damsté, Jaap S.
Abstract : Eight pure cultures of alkaliphilic haloaloarchaea capable of growth by dissimilatory sulfur reduction (previously only shown for neutrophilic haloarchaea) were isolated from hypersaline alkaline lakes in different geographic locations. These anaerobic enrichments, inoculated with sediments and brines, used formate, butyrate and peptone as electron donors and elemental sulfur as an electron acceptor 4 M total Na + and at pH 9–10. According to 16S rRNA gene sequencing, the isolates fell into two distinct groups. A major group, comprising seven obligate alkaliphilic isolates from highly alkaline soda lakes, represents a new species-level branch within the genus Natronolimnobius (order Natrialbales ), while a single moderately alkaliphilic isolate from the less alkaline Searles Lake forms a novel genus-level lineage within the order Haloferacales . The cells of the isolates are either flat rods or coccoid. They are facultative anaerobes using formate or H2 (in the presence of acetate or yeast extract as carbon source), C4 –C9 fatty acids or peptone (the major group) as electron donors and either sulfur or DMSO (the major group) as electron acceptors. Aerobic growth is only possible with organic acids and peptone–yeast extract. All isolates are extreme halophiles, growing optimally at 4 M total Na + . On the basis of their unique physiological properties and distinct phylogeny, we propose that the seven isolates from the soda lakes are placed into a novel species, Natronolimnobius sulfurireducens sp. nov. (type strain AArc1 T =JCM 30663 T =UNIQEM U932 T ), and the Searles Lake isolate, AArc-Sl T, into a new genus and species Halalkaliarchaeum desulfuricum (=JCM 30664 T =UNIQEM U999 T ).